KAJIAN ESTETIKA ARSITEKTUR FASAD PADA RUMAH TINGGAL DESA KENALI - Enjelina, Adelia; Putri, Andhini Laksita; Wahyuni, Diyah Arum (Jurnal Arsitektur ARCADE, 2021)
Abstract: The façade is the part that separates the outer and inner areas of the building, which can be interpreted as the leather or face layer of the building. Aesthetics is an architectural term for visually assessing a beauty in an architectural product, which has the value of abstract beauty. In assessing an aesthetic must have 3 things namely utility/ usability, firmness / robustness, and venusitas / beauty. Research using qualitative methods that compare observation results with existing theories. The building that was used as an object is the building of kenali village residence which is a development of the traditional house of pesagi. The purpose of this research is to analyze the aesthetics of the facade and typical facade according to the development of the times in the traditional house of Kenali Village. The elements of the facade are color, wall, ventilation, entrance, column, roof, signboard, balcony and staircase. The aesthetic value highlighted on the facade is the rhythm, composition, proportions, and symmetry shown by the arrangement and selection of openings, the material of the facade walls, and the arrangement of materials on the facade. The balance of aesthetic values on the façade of the building can make an interesting visual that has its own uniqueness.Abstrak: Fasad merupakan bagian yang memisahkan area luar dan dalam bangunan, yang dapat diartikan sebagai lapisan kulit atau muka dari bangunan. Estetika  merupakan istilah arsitektur dalam menilai suatu keindahan pada produk  arsitektur secara visual, yang memiliki nilai keindahan abstrak. Dalam menilai suatu estetika harus memiliki 3 hal  yaitu utilitas/kegunaan, firmitas/kekokohan, dan venusitas/keindahan. Penelitian dengan menggunakan metode kualitatif yang membandingkan  hasil observasi dengan teori yang ada. Bangunan yang dijadikan sebagai objek  adalah bangunan rumah tinggal Desa Kenali yang merupakan perkembangan dari  rumah tradisional pesagi. Tujuan dari penelitian ini adalah untuk menganalisis  estetika fasad dan tipikal fasad sesuai perkembangan zaman pada rumah tradisional  Desa Kenali. Elemen pembentuk fasad adalah warna, dinding, ventilasi, entrance, kolom,  atap, papan tanda, balkon dan tangga. Nilai estetika yang ditonjolkan pada fasad  adalah irama, komposisi, proporsi, dan simetri yang diperlihatkan dengan penyusunan dan pemilihan  bukaan, material dinding fasad, serta penataan material pada fasad. Keseimbangan  nilai estetika pada fasad bangunan dapat menjadikan suatu visual yang menarik yang memiliki keunikan tersendiri.